Pluralism Ethics as an Effort to Revitalize Pancasila Values Amidts of the Threat of National Disintegration - Indriani, Dwi Indah (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
The implementation of the ethics of pluralism as an effort to revitalize Pancasila values is motivated by problems arising from the nation itself, such as demonstrations that end in chaos, customs, ethnicity, religion, an area that is so vast that the logical consequence of these diverse orientations must be accepted and respected. If these symptoms are not addressed immediately, they could pose a danger of national disintegration. Thus, the ethics of pluralism is very important to teach good manners in an attitude of being willing to accept opinions in deliberations and consensus as the embodiment of democracy. Where the spirit of mutual cooperation and mutual respect for differences is applied in everyday life.